The only option for the poor? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Organic fertilizer may be the only type available to poor farmers, but it can help to restore their land and keep their crops alive during drought. The report comes from Malawi.